Faith-based health screenings for Marshallese adults living in the Republic of the Marshall Islands: Study design and results - Andersen, Jennifer A.; Rowland, Brett; O'Connor, Gail; Bing, Williamina Ioanna; Riklon, Sheldon; Mendoza-Kabua, Philmar; McElfish, Pearl A. (Frontiers in Public Health, 2023)
Introduction Striking health disparities exist in the Republic of the Marshall Islands (RMI). The RMI has one of the highest age-adjusted type 2 diabetes mellitus (T2DM) rates in the world (23.0%) compared to global (9.3%) and United States (US; 13.3%) rates. We conducted health screenings including clinical indicators of T2DM and hypertension among Marshallese in the RMI. Methods Screenings were conducted at 20 churches on Majuro Atoll. Participants completed questionnaires and biometric data collection assessing glycated hemoglobin (HbA1c), blood pressure, and body mass index. Results Screenings included 528 participants and showed a high prevalence of T2DM, obesity, and hypertension. One-third of participants were referred to the non-communicable disease clinic. The percent of adults in this study with T2DM-indicative HbA1c (48.5%) is higher than observed at the national level (23.0%). Discussion Results highlight the need for non-communicable disease-related programs in the RMI.